A liberdade de expressão e a magistratura: limites à atuação normativa do Conselho Nacional de Justiça no controle de comportamentos dos magistrados em redes sociais - Lima, Isaac Costa Soares de (2025)
The National Council of Justice, a correctional body of the Judiciary, with the scope of regulating the behavioral activity of magistrates, published the Resolution No. 305 of 17/12/2019. Such normative act restrict the freedom of expression of judges under the argument that they must have an impeccable and impeccable conduct, distinguishing themselves from other citizens. However, judges, like everyone else, are increasingly using social media as a way to express their points of view on the most diverse situations in life and the world. Such demonstrations, not infrequently, can lead to demonstrations of a political, religious or even ideological nature. The Constitution prohibited the magistrate from carrying out party political activity. However, the National Council of Justice has issued rules that aim to impose on the magistrate to behave in private life in a way that dignifies the role. In this context, using the qualitative and exploratory method, through bibliographic and jurisprudential review, the present work aims to compare and analyze, from the perspective of the right to expression, the right to personality as a general clause established in art. 1st, III, of the Federal Constitution, whether the Resolution No. 305 of 12/17/2019 of the National Council of Justice are compatible with the constitutional text.